Endoscopic ultrasound-guided celiac plexus neurolysis in pancreatic cancer-associated pain: different technical approaches in three challenging cases - Li Salvatierra, Bruno (2023)
Abdominal pain is severe in the vast majority of patients with pancreatic cancer. In some cases, chronic use of analgesics markedly reduces quality of life due to side effects. Endoscopic ultrasound-guided celiac plexus neurolysis is a procedure that controls cancerassociated pain in this population and consists of injecting a neurolytic agent around or within the celiac plexus. In this report, we present three cases with different technical approaches for celiac plexus neurolysis